A Development of English Proficiency Test of Undergraduate English Major Students of University of Phayao - Yeunsak, Sanit; Sriwichai, Chuanpit; Duangfai , Chanapa; Paichareon, Narisa (วารสารจิตวิทยาพุทธศาสตร์ประยุกต์เพื่อสังคม, 2022)
This study aimed to develop English proficiency tests for undergraduate English major students of School of Liberal Arts, University of Phayao based on CEFR C1 level and to evaluate the quality of the developed tests. Pursuing the research objectives, two versions of the tests had been developed and conducted. Each version of the test consisted of 60 items, and it was divided into 4 parts including vocabulary, reading, grammar and writing, and conversation. There were 15 items in each part. The samples of this study were 174 fourth-year English major students of the School of Liberal Arts, University of Phayao in academic year 2021. The content validity of the two tests was verified by the 3 experts in the fields of English language and Education Evaluation and Assessment using Index of Item-Objective Congruence (IOC). Then the tests were tried out with the samples to analyze difficulty and discrimination based on the 27 % technique of Chung Teh-Fan indicating that the criteria for an index of difficulty should be between 0.20 and 0.80 and the index of discrimination should be at least 0.20. Next, the tests were analyzed for reliability using KR-20 formula. The research results were as follows; For the first objective of the study; To develop University of Phayao Standard Test, the study resulted in the two versions of C1 Standard Test of English Proficiency which consist of 60 items in four parts; vocabulary, reading, grammar and writing and conversation respectively for the fourth years students in University of Phayao. For the second objective of the study: evaluating the quality of University of Phayao standard test of English proficiency C 1 level, the index of item objective congruence (IOC) which are satisfied with the mean level at over 0.50 expressed that version one of the tests ranging from 0.33 to 1.00, was at 0.94 of the IOC indexes mean, followed by the IOC index means of version two ranging from 0.67 to 1.00 at 0.99. Both versions reflected the high content validity. In terms of the standardized quality of the difficulties and the discrimination of the test, there were 57 qualified items in the first version of the tests, and all items are qualified in the second one. The reliability index of version one of the English proficiency test was at 0.82 and the value of version two was at 0.83 indicating that both tests reached acceptable reliability value.